The trajectory of vaginismus and its impact on the sex life of women in fertile period (Research, Society and Development, 2022)
Objective: To know the impact of vaginismus on the lives of women in menacme and the repercussions in the process of searching from diagnosis to treatment and cure. Methods: Research carried out through an online test in female participants of Brazilian nationality aged over 18 years and with diagnosis and/or previous report of signs of genito-pelvic pain/penetration (PPDDG). O considered the sex life of the intentionally based on the last six months, obtaining sociodemographic data; diagnosis, psychological relationship with sexual dysfunction (SD) and signs and symptoms of vaginismus; physiotherapeutic treatment and sexual life after healing. Results: After analyzing the jurors, it was observed that 78.6% of the women sought help on the internet to search for specialized professionals for the diagnosis, which was considered late for 15.6% who reported going through several professionals to be diagnosed, favoring thus the aggravation and symptoms of SD. Among the health professionals consulted by those guided in this study, the Pelvic Physiotherapist was the most referred for diagnosis (48.2%) and treatment (61.70%) and considering the trajectory until the desired cure was extensive, it was possible for 82 .2% of those intended to achieve penetration satisfactorily. Conclusion: The profile of this study confirms that vaginismus has a negative impact, interfering in the woman's life as a whole, altering physical, psychological, relational and social factors. Pelvic Physiotherapy proved to be active in assertively diagnosing women with vaginismus in a first consultation, making this specialization even more notorious and helpful in female pelvic dysfunctions, specifically vaginismus.